Resource manual to accompany nursing research : generating and assessing evidence for nursing practice - Polit, Denise F.; Beck, Cheryl Tatano (Philadelphia, Pennsylvania : Wolters Kluwer, Lippincott Williams & Wilkins, 2008)
This Resource Manual for the 8th edition of Nursing Research: Generating and Assessing Evidence for Nursing Practice complements and strengthens the textbook in important ways. The manual provides opportunities to reinforce the acquisition of basic research skills through systematic learning exercises, and in this edition we have placed particular emphasis on exercises that involve careful reading and critiquing of actual studies.
Part I: Foundations of nursing research and evidence-based practice -- Part 2: Conceptualizing a study to generate evidence for nursing -- Part 3: Designing a study to genrate evidence for nursing -- Part 4: Collecting research data -- Part 5: Analyzing and interpreting research data -- Part 6: Building an evidence base for nursing practice
Includes index.
Keywords: NURSING -- RESEARCH -- METHODOLOGY